2022
DOI: 10.1093/brain/awac117
|View full text |Cite
|
Sign up to set email alerts
|

Somatic variants in diverse genes leads to a spectrum of focal cortical malformations

Abstract: Post-zygotically acquired genetic variants, or somatic variants, that arise during cortical development have emerged as important causes of focal epilepsies, particularly those due to malformations of cortical development. Pathogenic somatic variants have been identified in many genes within the PI3K-AKT-mTOR-signaling pathway in individuals with hemimegalencephaly and focal cortical dysplasia (type II), and more recently in SLC35A2 in individuals with focal cortical dysplasia (type I) or non-dysplastic epilep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 81 publications
2
37
0
Order By: Relevance
“…Notably, the PTPN11 (c.1507G>A and c.1508G>T), KRAS (c.35G>A and c.35G>T), and BRAF (c.1797A>G and c.1799T>A) variants are all located in mutational hot spots for cancer and neurodevelopmental disorders. [19][20][21] However, except for KRAS c.35G>T and BRAF c.1799T>A, which have been reported in FCDs 22,23 and LEATs, 24 to our knowledge, none of the other somatic variants have been previously described in focal epilepsies. Both patients with NF1 somatic variants carried a diagnosis of neurofibromatosis type 1 and had known germline variants in the NF1 gene (c.499_502del and c.6904C>T) based on clinical testing.…”
Section: Pathogenic Somatic Variant Discovery and Brain Regional Enri...mentioning
confidence: 82%
“…Notably, the PTPN11 (c.1507G>A and c.1508G>T), KRAS (c.35G>A and c.35G>T), and BRAF (c.1797A>G and c.1799T>A) variants are all located in mutational hot spots for cancer and neurodevelopmental disorders. [19][20][21] However, except for KRAS c.35G>T and BRAF c.1799T>A, which have been reported in FCDs 22,23 and LEATs, 24 to our knowledge, none of the other somatic variants have been previously described in focal epilepsies. Both patients with NF1 somatic variants carried a diagnosis of neurofibromatosis type 1 and had known germline variants in the NF1 gene (c.499_502del and c.6904C>T) based on clinical testing.…”
Section: Pathogenic Somatic Variant Discovery and Brain Regional Enri...mentioning
confidence: 82%
“…[36][37][38][39] Somatic mutations in genes overlapping with some of the hyperexcitable variants identified in this study (PIK3CA, KRAS, PTEN, NF1, TSC2) have been reported in association with focal cortical dysplasia and drug-resistant epilepsy. 40 Indeed, the hyperexcitable gene set here demonstrated phenotypic enrichment of multiple brain malformations, suggesting the potential for similar epileptogenic mechanisms mediated by somatic mutations in gliomas. However, whether these genetic alterations contribute to epileptogenicity by the same mechanisms in different cell types is uncertain.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, pathogenic or likely pathogenic variants in CASK , KRAS , NF1 , and NIPBL were detected in patients with FCD type I. 35 In our center, we began to introduce somatic testing in diagnostic workup in 2019, and the numbers of patients examined continue to increase. In addition, somatic sequencing of brain tissue samples obtained in epilepsy surgery involves certain technical caveats.…”
Section: Discussionmentioning
confidence: 99%